Immunogenicity of a Monovalent Pandemic Influenza A H1N1 Virus Vaccine with or without Prior Seasonal Influenza Vaccine Administration - Igari, Hidetoshi (American Society for Microbiology, 2012)
The immunogenicity of pandemic influenza A H1N1 virus (A/H1pdm) vaccine might be modified by prior seasonal trivalent influenza vaccine (sTIV) administration. We conducted a retrospective analysis of immunogenicity of 243 health care workers (number of sTIV-positive [sTIV(+)] subjects, 216; number of sTIV(−) subjects, 27) by hemagglutination inhibition. There was no significant difference in the ratios of antibody titers of ≥40 (41.2% versus 48.1%; P = 0.49) and fold increases in geometric mean titer (3.8 versus 4.5; P = 0.37). sTIV injected 7 to 10 days prior to A/H1pdm vaccine administration did not interfere with the immunogenicity of the latter.